THE EPISTEMOLOGICAL BASIS OF THE PHILOSOPHY OF INFORMATION - Dr. Hamdan Hasan Al-Onizat, Dr. Towfic Louis Shomar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There have been several recorded developments of methodological pluralism in the research of Information Systems (IS) over the last three decades. Various disciplines, as well as many research communities, contributed to this discussion. Acting on the same subject of science or researching the same phenomena does not automatically allow for shared understanding. The epistemological assumed conclusions developed by various researchers will vary profoundly in this multidisciplinary and international context, in particular. These types of assumptions have a substantial effect on the understanding of concepts such as research reliability, validity, quality and rigour. Thus, the substantial publications of assumptions of epistemological conclusions are almost compulsory, in effect. The goal of this paper is therefore to establish an epistemological structure that can be used to examine epistemological claims in IS studies in a systematic way. Despite of trying to justify and recognize research paradigms of Information System, the current research aims at presenting a generic understanding of epistemological knowledge within the context of IS. The main focus of this research is to specify the elements that can be counted as basis to be able to recognize similarities along with the differences between separate methods and approaches of IS. The consensus-oriented interpretivist initiative to conceptual analysis is seen as a guide to explain the epistemological context..